2013
DOI: 10.1186/1744-859x-12-36
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in older elderly men with late-life depression and cardiovascular comorbidities: symptomatological correlation

Abstract: BackgroundWhether depression or cardiovascular disease would have a greater effect on worsening cognitive impairment in the burgeoning older elderly population is uncertain. Which disorder causes greater cognitive impairment was investigated.MethodsA cross section of 207 cognitively impaired older elderly (≥75 years old) men was recruited from outpatient clinics in southern Taiwan between 2004 and 2008. Their medical charts were reviewed for their history of medical illnesses, and those undergoing a current ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In a study of men over the age of 75 years, Chang and colleagues could not identify any difference between healthy and depressed subjects in the MMSE recall memory subscale (Chang et al, 2013), which is in accordance with findings of our work. In a study conducted by Elderkin-Thompson, the results of the delayed recall memory tests did not differ significantly between depressed and control individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study of men over the age of 75 years, Chang and colleagues could not identify any difference between healthy and depressed subjects in the MMSE recall memory subscale (Chang et al, 2013), which is in accordance with findings of our work. In a study conducted by Elderkin-Thompson, the results of the delayed recall memory tests did not differ significantly between depressed and control individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the prevalence of LLD, the growing oldest-old population and the impact of depressive syndromes on public health, few studies have specifically addressed the issue of cognitive dysfunction in oldest-old individuals with LLD (Xavier et al, 2001;Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, people ≥ 75 years old without depressive symptoms had better scores on cognitive tests than older adults with depressive symptoms. 31 On the other hand, depressive symptoms have always been closely associated with cognitive complaints and cognitive impairment. This topic is often controversial due to the discussion about whether depressive symptoms are responsible for cognitive decline or are part of the dementia process, as an initial symptom.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that late-life depression patients with comorbid CVDs showed a higher but non significantly different perseverative error in the Wisconsin Card Sorting Test measures than the group without CVDs (Chang et al, 2013), playing a role in the development of specific executive dysfunction (Rapp et al, 2005). In our study, we found that patients with late-life depression, comorbid CVDs, or related risk factors showed a higher rate of global cognitive deterioration than those without these comorbidities at one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%